Cornell University Faculty Handbook - Cornell Univ., Ithaca, NY.; Cornell Univ., Ithaca, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
The 1972 edition of Cornell University's faculty handbook details the organization of the university faculty; the administration organization and responsibilities; procedures for faculty appointments, promotions, tenure, dismissal, and retirement; faculty and administrative policies regarding faculty-student relationships; and campus facilities and services available. (JMF)
ERIC Note: Third edition.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Freedom; Administrative Organization; Administrative Policy; Administrator Responsibility; Affirmative Action; Ancillary Services; College Faculty; Committees; Faculty Handbooks; Faculty Organizations; Faculty Promotion; Fringe Benefits; Governance; Higher Education; Noninstructional Responsibility; Personnel Policy; Salaries; State Universities; Teachers; Tenure; Cornell University NY; Guides, General